Analisis Potensi Erosi DAS Sungai Merbau Dan DAS Sungai Ukui Terhadap Sedimentasi Danau Kayangan - Febiansyah, Dharma; Mudjiatko, Mudjiatko; Trimaijon, Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Land use change in Merbau and Ukui Watershed (DAS) as an effort to fulfill the need of land for settlement and other supporting infrastructure in Pekanbaru city will increase the potential oferosion and sedimentation in the watershed. This impact will have a major impact on the functional life of lake khayangan. Geographic information system is used to assist data analysis of land use,length and slope of land and vegetation distribution. The results of the analysis show the total erosion potential of the Merbau River Basin, the Ukui River Basin and the Direct Stream is 364,610tons / year and the total of sediments entering Lake Kayangan is 459,474 tons / year, with the elevation of siltation that occurs on Lake Kayangan is 0 , 22 mm / year.Keywords: land use change, erosion and sedimentation potential, siltation.